Pengembangan Jiwa Kewirausahaan Melalui Pelatihan Pembuatan Tas Decoupage - Melinda Malau; Rut Monica Desrianty; Yosya Sri Rotua Hutahaean (IKRA-ITH ABDIMAS, 2023)
Implementation Community Service aims to improve the economy and skills inconditions. Pandemic.COVID-19. This activity provides counseling about entrepreneurshipby carrying out activities for making Decoupage Bags, so that people who are not yeteconomically productive can wish to become entrepreneurs. Decoupage is an art craft withthe technique of cutting and pasting images from used materials (usually paper or tissue).The implication of implementing this Community Service is that people have talent inimproving the quality of goods that are of sale value, and have basic skills to start a businessso that they have an entrepreneurial spirit during the COVID-19 Pandemic